Review Artikel: Perkembangan Biosensor Dalam Mendeteksi Kandungan Babi (Sus scrofa) pada Produk Pangan untuk Verifikasi Kehalalan - Silfa Zakiyah; Siti Fatimah Azzahra (Jurnal Biodiversitas dan Bioteknologi, 2024)
Food processing in Indonesia and countries around the world is becoming increasingly complex. Food management must meet quality requirements, including nutritional fulfillment, safety and halal food products. Various analytical methods have been developed to test various products, both physically, chemically and biologically. Therefore, laboratory testing is needed to detect the presence of contaminants and non-halal ingredients in food products. This research discusses the detection of pork content in food products to support halal authentication. PCR and Biosensor methods are efficient and sensitive ways to ensure that food products are free from pork contamination. The Polymerase Chain Reaction (PCR) method allows the amplification of specific DNA from pigs, detecting even traces of DNA with high accuracy. Meanwhile, biosensors, which use antibodies or other biomolecular components, are able to detect pork proteins with high sensitivity through specific interactions with the target analyte. The method used is a literature review, conducting studies from various sources with the help of databases such as Connected Papers, ResearchGate, and Google Scholar with keywords such as "Detection of pork in food", "Regulation of halal food products", and "Biosensor for detecting pork content in food". This literature study used 40 journals selected based on the information needed